PERANAN AGAMA DALAM MEMBENTUK KELUARGA SAKINAH DALAM NOVEL AYAT-AYAT CINTA - Asep Supriadi (Balai Bahasa Sulawesi Selatan, 2013)
The literature of religion (Islam) had a religion value describing on Islamic rule. The literature of religion isan interesting object of research as there is a significant correlation between literature work and religion. Thereligion is the rule of God guiding and directs human being to the happiness in the world and beyond. It iscapable to determine offamily in sakinah, mawaddah, and rahmah. In order to discuss on the rule of religionto determine of sakinah family, used a descriptive-qualitative method based on verbal data of words, sentence,and discourse as depicted on the roman of Ayat-ayat Cinta. Establishing the family in sakinah, mawaddah, andrahmah can be realized when the religion being a principle of development. Mawaddah is love in honestly,rahmah is passionate, and sakinah is peacefull. It is accomplished by Fahri and Aisha to determine of familyin sakinah according to the true love, passionate, initiative, defensiveness, patient, sincere to the mercy of God. AbstrakSastra keagamaan (Islam) adalah sastra yang mengandung nilai-nilai ajaran agama, di dalamnya menggambarkannilai-nilai ajaran agama Islam. Sastra keagamaan menarik untuk dijadikan objek penelitian karena terdapatkaitan antara karya sastra dan agama. Agama adalah aturan-aturan Tuhan yang membimbing dan mengarahkanmanusia menuju kebahagiaan dunia dan akhirat. Dengan ajaran agama dapat membentuk keluarga sakinah,mawaddah dan rahmah. Untuk membahas peranan agama dalam membentuk keluarga sakinah dalam tulisanini digunakan metode deskriptif-kualitatif dengan bersumber dari data verbal berupa kata-kata, kalimat, danwacana yang terdapat dalam novel Ayat-Ayat Cinta. Dalam berumah tanggga akan terwujud rumah tangga yangmawadah, rahmah, dan sakinah jika agama dijadikan pedoman dalam membangun rumah tangga. Mawadahadalah perasaan cinta yang tulus, rahmah adalah kasih sayang, sedangkan sakinah adalah ketentraman ataukebahagiaan. Hal ini diwujudkan Fahri dan Aisha dalam membentuk keluarga sakinah yang didasari denganrasa cinta yang tulus, saling kasih sayang, berikhtiar, bertawakal, sabar, dan ikhlas. Serta mendapat rida Tuhan